The design, synthesis and characterisation of amine functionalised silica adsorbents for post combustion carbon capture - Starkie, Christopher (2016)
Amine functionalised silica adsorbents are promising materials for post combustion carbon capture. They exhibit high CO2 equilibrium adsorption capacities and selectively adsorb CO2 in the presence of water. A practical method of regenerating these materials in fossil fuel power stations is to utilise steam regeneration. There is a lack of understanding of the long term stability of amine functionalised silica in the presence of steam. This thesis explored the deactivation mechanism of impregnated and covalently tethered amine adsorbents under steam regeneration and humid adsorption conditions. The adsorbents were characterised using organic analysis and nitrogen sorption before and after aging. The effect of steam regeneration aging led to a significant decrease in the CO2 adsorption uptakes of the adsorbents. Impregnated amine adsorbents were deactivated by leaching of the impregnated amine component from the largest pores of the support. Steam aging also led to diminished amine accessibility caused by amine polymer agglomerating within pores below 8 nm. To address this issue of instability in the presence of steam amine impregnated silica adsorbents were post functionalised with organosilanes. Under certain conditions this silane functionalisation was shown to selectivity occur at the exterior and pore mouths of the adsorbent. The presence of silane coatings preserved the CO2 adsorption capacities of the adsorbents after aging. A compromise exists between adsorbent stability and CO2 uptake behaviour as silane functionalisation led to a reduction in the CO2 uptake capacity. Post functionalisation of amine impregnated silica with hydrophobic silanes limits the intrusion of water within the pores of the adsorbent. This reduction in water intrusion limits the rate of solubilisation of the amine polymer, thus preventing leaching. The impregnation of amine polymers onto porous silica supports typically leads to agglomerations and significant pore blocking. This limits the rate of adsorption and uptake capacity of the adsorbents. The introduction of aminesurfactant mixtures into the adsorbent was found to increase accessibility of the adsorption sites leading to enhanced rates of adsorption and CO2 equilibrium uptakes. The addition of surfactants also yielded a reduction in the regeneration requirements of the adsorbents, by the formation of favourable thin films of amine within the pores of the adsorbent